Coordinated maximum power point tracking in modular photovoltaic systems - Arriola, Nicolette Ann A.
Typically, photovoltaic (PV) systems are implemented as modular systems. Two major challenges in implementing PV systems is partial shading and transient irradiance conditions, while the structure of modular systems are prone to uneven degradation of modules when load sharing is not managed. In this study, a modular photovoltaic system was built wherein each module has an independent array of series-strung panels, and the system output is loaded with a 48-V battery bank and a constant DC load. The implementation of a DC communications bus in the system, for coordination among modules, was demonstrated to be advantageous in speed of recovery from transient irradiance changes during maximum power point tracking, as well as in load sharing control. Furthermore, partial shading conditions are addressed with a hardware approach. By implementing per-panel maximum power point trackers, wasted potential power from the solar panels under partial shading conditions is minimized.